2014
DOI: 10.1353/jhe.2014.0035
|View full text |Cite
|
Sign up to set email alerts
|

The Higher Education We Choose, Collectively: Reembodying and Repoliticizing Choice

Abstract: Reviewing three key areas of literature in our field (college choice, state policy, and faculty) the article identifies gaps that we can fill by reembodying and repoliticizing "choice," by which is meant moving beyond the individualized and "neutral" market logic in addressing the actions of collective entities in relation to politically charged policy issues, which we largely overlook. In calling our field to focus more on the "the higher education we choose," the article suggests reframing the prevailing pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Several researchers (Griffith & Rothstein, 2009; Turley, 2009) have found that students from low-income households were more likely to attend colleges in close proximity to their homes and argued the need for paying particular attention to what types of colleges are located in what types of areas. The interconnections of college admissions policies focusing on merit and the selective institutions recruitment and marketing to particular populations reveals that colleges are choosing higher income students (Rhoades, 2014), which is contradictory to the proportion of students graduating from underfunded schools in predominantly low-income areas with high concentrations of students of color (Frankenberg, 2013). Earlier studies support the current finding that proximity increases applicant odds of enrolling at institutions closer to home.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers (Griffith & Rothstein, 2009; Turley, 2009) have found that students from low-income households were more likely to attend colleges in close proximity to their homes and argued the need for paying particular attention to what types of colleges are located in what types of areas. The interconnections of college admissions policies focusing on merit and the selective institutions recruitment and marketing to particular populations reveals that colleges are choosing higher income students (Rhoades, 2014), which is contradictory to the proportion of students graduating from underfunded schools in predominantly low-income areas with high concentrations of students of color (Frankenberg, 2013). Earlier studies support the current finding that proximity increases applicant odds of enrolling at institutions closer to home.…”
Section: Literaturementioning
confidence: 99%
“…Traditional factors of higher education admission (Carnevale & Rose, 2003), college access and choice privilege middle - and higher-income populations (Kezar, 2011) who are more likely to be White. Furthermore, “policymakers and colleges choose communities/students, not just vice versa” (Rhoades, 2014, p. 919). Researchers have largely overlooked the impact of urban depopulation and increased suburbanization on Black and Latina/o local college access and choice.…”
mentioning
confidence: 99%
“…States have a more direct ability to develop and implement policies that impact higher education; historically states have provided the legal framework within which public and private institutions operate (McGuinness, Jr., 2011). Growing gaps in state educational funding, opportunity, and attainments are one of higher education's most serious issues (ASHE 2010;Finney, Perna & Callan, 2014;Jackson, 2007;Lindsay, 1988;Rhoades, 2014). States have been required to develop policies that comply with federal law concerning higher education.…”
Section: Rationale and Role Of Federal/state Policies In Expanding Edmentioning
confidence: 99%
“…Both of these theories underscore the role of signals of degree progress and academic fit at 2 and 4-year schools in shaping students' educational expectations. The standards of progress and performance that students are held to during the first year of college are constructed around privileged students and do not consider the diversity in academic experiences and behaviors for students from different backgrounds (Karabel, 1972;Rhoades, 2014;Tinto, 2012), including students with health impairments.…”
Section: Signals Shape Educational Expectationsmentioning
confidence: 99%
“…Both of these theories underscore the role of signals of degree progress and academic fit at 2 and 4-year schools in shaping students' educational expectations. The standards of progress and performance that students are held to during the first year of college are constructed around privileged students and do not consider the diversity in academic experiences and behaviors for students from different backgrounds (Karabel, 1972;Rhoades, 2014;Tinto, 2012), including students with health impairments.The transition to college may also differ between types of health impairments. Scholars categorize health impairments as "apparent" and "non-apparent", "visible" and "invisible" and "non-cognitive" and "cognitive" to separate the diverse experiences of mental versus physical impairments (Adams & Proctor, 2010; Frazier, Youngstom, Glutting, & Watkins, 2007;Fuller, Bradley, & Healey, 2004;Fuller et al, 2009;Mullins & Preyde, 2013;Murray, Lombardi, & Kosty, 2014;Olney & Brockelman, 2003;Wessel, Jones, Markle, & Westfall, 2009).…”
mentioning
confidence: 99%